Impaired autonomic function in normotensive obese children - Latchman, Peter L; Mathur, Madhu; Bartels, Matthew N; Axtell, Robert S; Meersman, Ronald E De (Clinical Autonomic Research, 2011)
Purpose To evaluate baroreflex sensitivity and autonomic control in a cohort of normotensive obese (OB) children. Method A cross-sectional investigation, in which, baroreflex sensitivity and autonomic control were evaluated using transfer function and power spectral density analysis (PSDA) of the electrocardiogram and beat-to-beat blood pressures in normotensive OB children and normal weight normotensive controls. All methods used were noninvasive and data were captured while seated and at rest. Results The OB and control subjects non-obese (NO) were of similar age (OB 9.1 ± 1.9 years vs.NO9.2 ± 1.4 years). The OB group was classified as having a BMI greater than the 95th percentile adjusted for age and gender, and a NO group with a BMI at or less than the 95th percentile (BMI percentile OB. 97.5 ± 1.3 vs. NO 58.5 ± 24.1). Both groups had similar normotensive blood pressures. T tests revealed that baroreflex sensitivity and HFRR were significantly reduced in the OB 9.2 ± 2.7 vs. 15.2 ± 4.7 (ms/mmHg) and 6.7 ± 1.1 vs. 8.2 ± 1.1 ms 2, respectively, while LF SBP and LF/HF ratio were significantly increased in the OB 11.9 ± 5.6 vs. 8.2 ± 4.7 mmHg 2 and 1.2 ± 0.7 vs. 0.54 ± 0.3, respectively. Conclusions Normotensive OB children exhibited significantly reduced baroreflex sensitivity, parasympathetic control as well as increased sympathetic control when compared with healthy, NO controls. Findings in this investigation raise the awareness that autonomic dysfunction is present in young OB normotensive children. © Springer-Verlag 2011.
Keywords: Autonomic Nervous System; Autonomic modulation; Baroreflex sensitivity; Blood Pressure; Child; Cross-Sectional Studies; Female; Humans; Male; Normotensive; Obese children; Obesity; article; autonomic dysfunction; blood pressure; blood pressure measurement; body mass; body weight; child; clinical article; controlled study; dept.hms; electrocardiogram; female; human; male; obesity; pressoreceptor reflex; school child; sensitivity analysis

Cardiovagal tone: A predictor of heart rate adjusted augmentation index in men but not in women - Latchman, Peter L.; Thiel, Robert; Gates, Gregory; Zhu, Weili; Axtell, Robert; Gardner, Kenneth; Lunn, William; DeMeersman, Ronald (Open Journal of Molecular and Integrative Physiology, 2017)
Keywords: dept.hms; peer-reviewed

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

Spontaneous baroreflex sensitivity in normotensive African-American men - Latchman, Peter L.; Gates, Gregory J.; Thiel, Robert; Axtell, Robert S.; Zhu, Weili; Morin-Viall, Ally; Yue, Tianhong; Yang, Qin; Gardner, Kenneth; Meersman, Ronald E. De (Open Journal of Molecular and Integrative Physiology, 2019)
Keywords: dept.hms; peer-reviewed